Study of the possible link of 25‐hydroxyvitamin D with Epstein–Barr virus and human herpesvirus 6 in patients with multiple sclerosis. (3rd August 2018) - Pérez‐Pérez, S.; Domínguez‐Mozo, M. I.; García‐Martínez, M. Á.; Aladro, Y.; Martínez‐Ginés, M.; García‐Domínguez, J. M.; López de Silanes, C.; Casanova, I.; Ortega‐Madueño, I.; López‐Lozano, L.; Torrejón, M. J.; Arroyo, R.; et al.
Abstract : Background and purpose: Although the causes of multiple sclerosis (MS) remain partially unknown, environmental and genetic factors are thought to play a role in its aetiopathogenesis. Hypovitaminosis D, Epstein–Barr virus (EBV) and human herpesvirus 6 (HHV‐6) infections have been described as possible MS triggers. Our aim was to analyse the possible link between 25‐hydroxyvitamin D [25(OH)D] and viruses in patients with MS. Methods: We included 482 patients with MS in a 2‐year study. Serum samples were collected to analyse 25(OH)D levels and, according to sample availability, antibody titres against EBV and HHV‐6 by enzyme‐linked immunosorbent assay. DNA was extracted from blood in order to analyse EBV and HHV‐6 viral load by quantitative real‐time polymerase chain reaction and to genotype MS‐related single nucleotide polymorphisms (rs3135388, rs2248359 and rs12368653) when possible. Results: The 25(OH)D levels were significantly higher in the first semester of the year than in the second. Carriers of the risk allele rs2248359‐C showed lower 25(OH)D levels than non‐carriers. For EBV, viral load was significantly higher when 25(OH)D levels were low, demonstrating an inverse correlation between 25(OH)D levels and EBV load. Conclusions: The 25(OH)D levels could be involved in the regulation of EBV replication/reactivation in patients with MS.